Plant species, not climate, controls aboveground biomass O2:CO2 exchange ratios in deciduous and coniferous ecosystems. Issue 9 (9th September 2017) - Gallagher, Morgan E.; Liljestrand, Frasier L.; Hockaday, William C.; Masiello, Caroline A.
Abstract: The oxidative ratio (OR) is the O2 :CO2 ratio associated with photosynthesis, respiration, and other ecosystem gas exchange processes and can be reported on the scale of an individual leaf, an ecosystem, up to the entire terrestrial biosphere. The OR of the terrestrial biosphere is used to partition anthropogenic CO2 between oceanic and terrestrial carbon sinks, and the ease of measurement of this property on smaller scales suggests its potential for other uses. However, controls on the natural variation of OR are not understood in either organic matter pools or fluxes, and this lack of basic information limits the use of the tracer. Here we assess the annual variability of the OR of photosynthesis over ~decade for two temperate forests, one coniferous and one deciduous, and show that the photosynthetic OR signature is strongly dominated by plant species. We determined the OR of this flux by measuring the OR of carbon pools that close on annual or shorter timescales (leaves and individual tree rings), via solid‐state 13 C NMR spectroscopy and elemental analysis. Leaf litter OR is different between coniferous and deciduous forests, but tree bole OR is constant between species. There was no significant change in leaf litter OR with time, nor any correlations between leaf litter OR and temperature or precipitation. During this time growing season precipitation varied by 95% from the time period average, and growing season temperature by 22%, demonstrating that on the decadal scale photosynthetic OR is invariant over significant shifts in these climate parameters. Key Points: Oxidative ratio (O2 :CO2, OR) for the production of aboveground biomass in a Michigan coniferous forest was 1.069 ± 0.014 over 8 years OR for aboveground deciduous forest biomass was 1.038 ± 0.006 over the same time period Large variations in growing season precipitation and temperature did not show any influence on aboveground biomass OR